2018
DOI: 10.1002/tcr.201800115
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Materials, used in Energy Storage Applications: the Quest for Robust and Accurate Computational Methodologies

Abstract: Study of materials, used as constituents for energy storage devices (e. g. Li‐ or Na‐ion batteries) has been greatly enhanced by the first principles theoretical modeling. As a prerequisite, accurate computational framework should be employed in order to provide adequate description of studied materials in close agreement with available experimental data. In this account we present our approach to formulation of a suite of computational techniques, that can be used for accurate evaluation of key materials prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Evaluation of the U parameter computationally, particularly using the linear response method, is an alternative approach, which permits determination of U , fully avoiding fitting to experimental data. Previous works, including several performed by us, , have shown that average redox voltages can be calculated with a reasonable accuracy for various cathode materials, adopting the values of U parameters determined using linear response parametrization.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the U parameter computationally, particularly using the linear response method, is an alternative approach, which permits determination of U , fully avoiding fitting to experimental data. Previous works, including several performed by us, , have shown that average redox voltages can be calculated with a reasonable accuracy for various cathode materials, adopting the values of U parameters determined using linear response parametrization.…”
Section: Introductionmentioning
confidence: 99%